2012
DOI: 10.1111/1468-0106.12006
|View full text |Cite
|
Sign up to set email alerts
|

Income Heterogeneity in the Voluntary Provision of Dynamic Public Goods

Abstract: This paper explores the effect of income inequality on the voluntary contributions to a dynamic public good. We find that income heterogeneity has a significant impact both on contributions and welfare. The results show that the often observed decay of cooperation does not carry over to the asymmetric environment considered in this study. Our results also suggest that subjects in each income class make different contribution amounts in an absolute sense and give the same percentage of their income. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Consequently, with punishment, low-benefit members did not benefit from being part of a privileged group. Secilmis & Gü ran [115] studied the effects of differences in endowment. They observed higher average contributions in egalitarian groups.…”
Section: (Iv) Experimental Gamesmentioning
confidence: 99%
“…Consequently, with punishment, low-benefit members did not benefit from being part of a privileged group. Secilmis & Gü ran [115] studied the effects of differences in endowment. They observed higher average contributions in egalitarian groups.…”
Section: (Iv) Experimental Gamesmentioning
confidence: 99%
“…Other public goods experiment-based studies suggest that economic heterogeneity is likely to have a deleterious impact on collective action (Anderson et al, 2008;Fung & Au, 2014;Seçilmiş & Güran, 2012), especially when individuals are aware of differences in wealth levels (Anderson et al, 2008). Given subjects having full information and the absence of corrective institutions, we, thus, hypothesize that wealth heterogeneity undermines collective action: Rapoport & Suleiman, 1993;Visser & Burns, 2015).…”
Section: Theimpactofwealthheterogeneityoncbcmentioning
confidence: 89%
“…In linear public goods games, however, Chan et al (1996, 1999) and Hofmyer et al (2007) find little effect on group cooperation as wealth heterogeneity increases. Other public goods experiment‐based studies suggest that economic heterogeneity is likely to have a deleterious impact on collective action (Anderson et al, 2008; Fung & Au, 2014; Seçilmiş & Güran, 2012), especially when individuals are aware of differences in wealth levels (Anderson et al, 2008). Given subjects having full information and the absence of corrective institutions, we, thus, hypothesize that wealth heterogeneity undermines collective action:H1 Wealth heterogeneity hypothesis: Under conditions of full information, the presence of endowment heterogeneity will decrease groups' overall rate of contribution to collective action.…”
Section: Hypothesesmentioning
confidence: 99%
“…However, most of the existing literature has ignored features that are present in many development settings such as high degrees of inequality and subsistence poverty limiting the ability of some people in the group to contribute to the public good. Absent lottery incentives, past studies have found that an increase in inequality is often associated with reduced cooperation and provision of public goods (e.g., Cardenas, 2003; Cherry et al, 2005; Fung & Au, 2014; Gächter et al, 2017; Hargreaves Heap et al, 2016; Keser et al, 2014; Nitta, 2014; Rapoport, 1993; Seçilmiş & Güran, 2012). Should the negative effects of inequality extend to lottery funding mechanisms as well, then the practical promise of such procedures may be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the success of lotteries in encouraging contributions to public goods in the laboratory can be translated into an effective tool in assisting developing communities depends, at least in part, on how factors such as inequality and subsistence poverty interact with the performance of such lottery schemes. Past research on inequality has generally found it to have a negative impact on investments with standard voluntary contributions mechanisms (e.g., Balafoutas et al, 2013;Cadigan et al, 2011;Cherry et al, 2005;Fung & Au, 2014;Hargreaves Heap et al, 2016;Keser et al, 2014;Nitta, 2014;Rapoport, 1993;Seçilmiş & Güran, 2012;and Gächter et al, 2017) although some have found inequality to have no effect (e.g., Bergstrom et al, 1986;Buckley & Croson,2006;Chan et al, 1996Chan et al, , 1999Hofmeyr et al, 2007). 4 Given that inequality can be quite stark in many developing communities, if inequality has a negative effect for lottery funding mechanism it would cast doubt on the ability of such schemes to work in development contexts.…”
Section: Introductionmentioning
confidence: 99%